IMF Research Bulletin, March 2008. (IMF Research Bulletin; IMF Research Bulletin ;, 2008)
IMF research summaries on foreign direct investment (by Yuko Kinoshita) and on trade linkages and business cycles (by Julian di Giovanni and Andrei Levchenko); country study on Mexico (by Roberto Garcia-Saltos); listing of visiting scholars at the IMF during February-June 2008; listing of contents of Vol. 55, Issue No. 1 of IMF Staff Papers; listing of recent IMF Working Papers; and a listing of recent external publications by IMF staff.